Classroom assessment concepts and applications - Russell, Michael K. 1967-; Airasian, Peter W.; Airasian, Peter W. (New York, N.Y. McGraw-Hill, 2012)
"Assessment is a daily, ongoing, integral part of teaching and learning. Classroom Assessment: Concepts and Applications explores how assessment is a key component of all aspects of the instructional process, including organizing and creating a classroom culture, planning lessons, delivering instruction, and examining how students have grown as result of instruction. The text also introduces preservice teachers to new tools and approaches to classroom assessment that result from the infusion of computer-based technologies in schools. This is the most teacher friendly assessment textbook available one that will inform a teachers assessment practices for years to come"-- Provided by publisher.
Machine generated contents note: Chapter 1: The Breadth of Classroom Assessment Chapter 2: Learning About Students: Early Assessment Chapter 3: Lesson Planning and Assessment Objectives Chapter 4: Formative Assessment Chapter 5: Summative Assessments Chapter 6: Designing, Administering, and Creating Achievement Tests Chapter 7: Universal Design for Assessment Chapter 8: Performance Assessments Chapter 9: Grading Chapter 10: Commercial Standardized Achievement Tests Chapter 11: Computer-Based Technology and Classroom Assessment Appendix A: Standards for Teacher Competence in Educational Assessment of Students Appendix B: Taxonomy of Educational Objectives (Major Categories and Illustrative Objectives) Appendix C: Sample Individual Education Plan Appendix D: Statistical Applications for Classroom Assessment Appendix E: Some Resources for Identifying Special Needs Glossary References Name Index Subject Index.
Rev. ed. of: Classroom assessment / Peter W. Airasian, Michael Russell. c2008.
Machine generated contents note: Chapter 1: The Breadth of Classroom Assessment Chapter 2: Learning About Students: Early Assessment Chapter 3: Lesson Planning and Assessment Objectives Chapter 4: Formative Assessment Chapter 5: Summative Assessments Chapter 6: Designing, Administering, and Creating Achievement Tests Chapter 7: Universal Design for Assessment Chapter 8: Performance Assessments Chapter 9: Grading Chapter 10: Commercial Standardized Achievement Tests Chapter 11: Computer-Based Technology and Classroom Assessment Appendix A: Standards for Teacher Competence in Educational Assessment of Students Appendix B: Taxonomy of Educational Objectives (Major Categories and Illustrative Objectives) Appendix C: Sample Individual Education Plan Appendix D: Statistical Applications for Classroom Assessment Appendix E: Some Resources for Identifying Special Needs Glossary References Name Index Subject Index.
Purita Baltazar (Recommending Faculty) : Social Sciences Cluster
Keywords: Educational tests and measurements -- United States; Academic achievement -- United States -- Testing; Education -- United States -- Evaluation